Urdu Translation and Validation of 12- Item Multiple Sclerosis Walking Scale - Hira Rafique, Misbah Waris, Sania Maqbool,Warda Shafique,Sadia Sukhera, Saimoon Rafi, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The MSWS-12 is a useful patient based tool for testing gait in people with MS. It accounts for patient’s own perspective that how their disease has affected their gait. It has been cross-culturally adapted and validated in 51 languages as Italian, Brazilian, Turkish, Korean and Persian. Aim: To adapt and translate MSWS-12 in Urdu language and to check the validity and reliability of resultant Urdu version on group of MS patients. Methodology: The Study was conducted in two phases. First phase included its translation in Urdu language which was done according to Beaten et al Criteria. Which includes 5 main steps as forward translation, translation consolidation, backward translation, review by the committee and application of final version. In second phase validity and reliability was assessed. The study included patients with MS between age of 20-50 years who can read and understand Urdu language. Results: The current Urdu version of MSWS-12 demonstrated great compatibility with the original English version. The MSWS-12-U showed excellent reliability and validity, having ICC value 0.979, while Cronbach’s alpha value of 0.90 and 0.979 for test and retest respectively. For validity, CVI score for MSWS-12-U was 0.91. MSWS-12-U showed excellent correlation with TUG having R-value and Rho values of 0.950 and 0.935 respectively. Factor analysis showed that total and commutative variance was 87.665%. Practical implication: The Urdu version of MSWS-12 will help medical professionals including physical therapist to collect the data more accurately so that they can evaluate patient reported walking difficulties in MS patients. Conclusion: The study concluded that MSWS-12-U is highly reliable and a valid tool. Key words: Multiple Sclerosis,Walking impairments, MSWS-12, walking assessment